2016
DOI: 10.1097/ico.0000000000000841
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Therapeutic Penetrating Keratoplasty Using Glycerol-Preserved Donor Corneas in Infectious Keratitis

Abstract: TPK using glycerol-preserved corneas has a high rate of secondary glaucoma and recurrence of infection with unsatisfactory visual results. These corneas may be used as temporary emergency transplants in infectious keratitis when fresh corneas are unavailable to meet demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
1
7
0
4
Order By: Relevance
“…Compared with fresh donor corneas, glycerol-preserved corneas have several potential advantages, such as increased availability, weak graft rejection and low risk of microbial contamination [21]. Glycerol-preserved corneas, with a graft size ranging from 2 to 8 mm [22] and 7 to 10 mm [23], had been applied for TPK in infectious keratitis, which showed postoperative complications such as reinfection, secondary PK, opacification or glaucoma. Shi et al [13] reported cases treated eccentric corneal perforations by PK using glycerol-preserved small-diameter corneal grafts (2.5–4.5 mm), which showed all grafts remained clear at the end of a follow-up period from 7 to 36 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with fresh donor corneas, glycerol-preserved corneas have several potential advantages, such as increased availability, weak graft rejection and low risk of microbial contamination [21]. Glycerol-preserved corneas, with a graft size ranging from 2 to 8 mm [22] and 7 to 10 mm [23], had been applied for TPK in infectious keratitis, which showed postoperative complications such as reinfection, secondary PK, opacification or glaucoma. Shi et al [13] reported cases treated eccentric corneal perforations by PK using glycerol-preserved small-diameter corneal grafts (2.5–4.5 mm), which showed all grafts remained clear at the end of a follow-up period from 7 to 36 months.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some researchers have found that the residual corneal endothelial cells beyond the perforation may migrate and cover the posterior graft surface after PK with glycerol-preserved corneas [13]. Therefore, an increasing number of investigators in different countries are trying to use glycerol-preserved donor corneas for therapeutic penetrating keratoplasty (TPK) in patients with corneal perforations [13, 22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Hyphema was associated with surgical delay and the use of large graft, and was often due to the presence of refractory infection and multiple neovascularization 24. A large graft was a significant associated factor for graft rejection 21. In the present study, the diameter of graft was often equal to or larger than 8.75 mm (389/561, 69.3%), which was due to the extensive range of severe infiltration.…”
Section: Discussionmentioning
confidence: 49%
“…In our study cryopreserved corneas were used as emergency keratoplasty for severe keratitis with perforation or that affected the limbus and sclera when no fresh donor cornea was available. Other reports also demonstrated that cryopreserved donor corneas could be effectively applied for TKP even in patients with a large corneal perforation 20,21. The use of cryopreserved donor corneas was also necessary in view of the extreme shortage of donor corneas in China 19…”
Section: Discussionmentioning
confidence: 99%
“…28,29 A recent case series of therapeutic PK using glycerolpreserved corneas performed for infectious keratitis, in which fungal etiology accounted for the majority of cases, showed that almost 41% of eyes required evisceration or enucleation. 30 The indication for such an early surgical approach comes from the authors' desire of not ' losing' any eye because of complications such as endophthalmitis, phthisis, or evisceration, and neither to perform a PK that has definitely lower graft survival and higher risk of more severe complications than DALK. 31…”
Section: Discussionmentioning
confidence: 99%